Relasjoner ved enden av Regnbuen (1953) - Simonsen, Anne Hege (Nordlit, 2020)
In her autobiography The Rainbow Marie Hamsun gave her husband Knut a mind, a body and a family. She brought the public an “inside view” and was rewarded with public reverence, in spite of her background as a non-repenting Nazi. Book reviews from October 1953 show how the (overwhelmingly) male reviewers embraced the book as an opportunity to "take back Hamsun", despite his Nazi affiliations. They were to a lesser extent interested in the book as Marie Hamsun's own literary project. This is echoed in the research on Hamsun where the book is frequently cited as a source, but only to a small extent referred to as literature. This article examines The Rainbow as an act of communication in which the author's intention and readers' acknowledgments are seen as relational.